Assessing the risk of Obstructive Sleep Apnea in Type 2 Diabetes Mellitus patients in India - Kovila Rajiv; Vinuthna Reddy Lakshmi; Marfatia Ansh (Journal of Sleep And Sleep Disorder Research, 2024)
Background/Aim Obstructive Sleep Apnea (OSA) is a prevalent disorder characterized by recurrent respiratory disturbances during sleep. Patients with Type 2 Diabetes Mellitus (T2DM) and obesity exhibit a substantial susceptibility to OSA (23%–86%). People with OSA have a high risk of several comorbidities like insulin resistance, cardiovascular disease, depressed mood and hypertension. Thus, the objective was to comprehensively evaluate the risk of OSA among T2DM patients in India. Materials and Methods A cross-sectional survey was conducted across four cities in India involving 2,000 T2DM patients. The survey gathered data on patient demographics, clinical endpoints, and estimated the risk of OSA using an app which included the STOP BANG questionnaire. Multivariate logistic regression analysis was used to evaluate the association between OSA risk and key variables such as age, gender, BMI, and HbA1c. Result Overall, 63.9% of T2DM patients were identified as high risk and 27.3% were at intermediate risk for OSA development. Results of the multivariate logistic regression demonstrated that patients with high BMI ≥35 had significantly greater odds (OR: 5.70; p<0.00) of developing OSA; males had 2.75 times higher odds (p<0.00) and patients with HbA1c value >8% had higher odds (OR: 1.22; p<0.00) of developing OSA. Conclusion OSA risk and prevalence are significantly higher in T2DM patients than in the general population with a notable escalation in patients who are overweight/obese, older, and have prolonged diabetes duration. Early screening using digitalization with a highly sensitive, cost-efficient, and valid tool like STOP-BANG followed by appropriate intervention for OSA can not only reduce the eventual economic burden but can improve patient outcomes.
Keywords: Obstructive Sleep Apnea